NUMERICAL ANALYSIS OF EARLY AGE MOVEMENT IN GROUTED CONNECTIONS. Issue 1 (26th April 2023) - Henneberg, J.; Schaumann, P.
Abstract: Grouted connections (GC) of offshore structures are susceptible to wave loading and current directly after grouting. Early age movement (EAM) during the curing process can affect the material properties and the interface quality between the grout and the steel structure. Such effects were observed in laboratory tests performed at the Leibniz University Hannover. Generally, EAM can be characterised by high shear rates and identified as a damage mechanism. In this contribution, the authors present a numerical approach that transfers the observed damage mechanism into an ultimate strength analyses of the GCs. For this purpose, EAM simulations and laboratory tests with fluid grout material are combined to determine areas of high shear rates, which mainly affect the grout properties. With an element‐based adjustment approach, the material law of each element is adjusted according to the level of shear rate. The adjusted finite element model is analysed on its maximum axial load resistance.